2012
DOI: 10.21236/ada566090
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Tailored Adaptive Personality Assessment System (TAPAS) as an MOS Qualification Instrument

Abstract: This report examines whether the Tailored Adaptive Personality Assessment System (TAPAS) may be useful for selecting and classifying recruits into Military Occupational Specialties (MOS) and describes the two broad approaches that were taken to evaluate the measure for these purposes. TAPAS data for this research were collected from Army applicants at the Military Entrance Processing Stations (MEPS) between May 2009 and June 2011. In addition, criterion data were collected in the Tier One Performance Screen (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…It is no longer just a tool for educational psychologists to assess right or wrong answers. For example, IRT has become ubiquitous in large-scale testing practices such as military selection (e.g., Nye et al, 2014) and is seeing growing use among clinicians (Reise & Waller, 2009). Additionally, a more unified framework for using IRT, namely, within the software R, is beginning to develop.…”
Section: Conclusion: Lessons Learned and Advice To Move Forwardmentioning
confidence: 99%
“…It is no longer just a tool for educational psychologists to assess right or wrong answers. For example, IRT has become ubiquitous in large-scale testing practices such as military selection (e.g., Nye et al, 2014) and is seeing growing use among clinicians (Reise & Waller, 2009). Additionally, a more unified framework for using IRT, namely, within the software R, is beginning to develop.…”
Section: Conclusion: Lessons Learned and Advice To Move Forwardmentioning
confidence: 99%
“…Between 2006 and 2008, the Tier 2 Attrition Screen (TTAS) allowed for more tier 2 contracts (Heffner, Campbell, and Drasgow, 2011). TTAS was the forerunner to TAPAS, which aims to identify prospects with desirable attributes, such as commitment, drive, personality, and leadership, that are not measured solely by the Armed Services Vocational Aptitude Battery (ASVAB) or the AFQT, which is based on a subset of ASVAB scores (Nye et al, 2012). Initial operational test and evaluation of TAPAS began in 2009 on several large occupational specialties, including infantry, military police, combat medics, and motor transport operators.…”
Section: Modeling the Relationship Between Recruiting Rate And Rmc/wamentioning
confidence: 99%
“…As noted in Section 2, the military services have begun to use TAPAS, a personality assessment that was originally developed for the U.S. Army Nye et al, 2012). This assessment contains 21 facets of the Big Five personality traits and may expand to include additional facets of interest to the U.S. military (see Table 3.2).…”
Section: Tailored Adaptive Personality Assessment Systemmentioning
confidence: 99%
“…Specifically, Nye et al (2012) found that patterns across TAPAS scales differed across Army MOSs, suggesting that the TAPAS may help choose individuals for different MOSs (see also Drasgow et al, 2012). Nye et al also found that TAPAS scales were significantly associated with job knowledge, Army Physical Fitness Test scores, disciplinary incidents, and attrition.…”
Section: Tailored Adaptive Personality Assessment Systemmentioning
confidence: 99%